Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Ukuran Perusahaan dan Leverage terhadap Integritas Laporan Keuangan - Widya Kusuma Wardhani; Yuli Chomsatu Samrotun (Universitas Batanghari Jambi, 2020)
The study aims to determine the effect of institutional ownership, managerial ownership, company size and leverage on the integrity of financial statements. Dependent variable in this study are integrity of financial statements while the independent variables used in this study are institutional ownership, managerial ownership, company size and leverage. This research is focused on mining companies on the Indonesia Stock Exchange (IDX) period 2013-2018. The selection of samples in this study used the purposive sampling method, this obtained a sample of 54 sample data from the mining companies population listed on the Indonesia Stock Exchange (IDX) period 2013-2018. The analytical tools used in this study are multiple linear regression analysis. The results of this research show that the variable institutional ownership affect the integrity of financial statements, while the managerial ownership variables, company size and leverage do not affect the integrity of financial statements.